Towards a Universal Pension Points System in France - Hervé Boulhol (Intereconomics, 2020)
A specificity of the current French system is that a private sector worker is currently covered by two mandatory public pay-as-you-go (PAYGO) schemes: a general defined benefit (DB) scheme – which is the main component – managed by the state and a points scheme (AgircArrco) managed by social partners, together representing about 70% of paid benefits.
Keywords: 330